Cold atmospheric pressure plasma‐assisted removal of aflatoxin B1 from contaminated corn kernels. Issue 1 (25th October 2020) - Hojnik, Nataša; Modic, Martina; Žigon, Dušan; Kovač, Janez; Jurov, Andrea; Dickenson, Aaron; Walsh, James L.; Cvelbar, Uroš
Abstract: Mycotoxins, the toxic secondary metabolites produced by filamentous fungi, are found in up to 80% of global food and feed crops. Here, we report on the complete removal of aflatoxin B1 (AFB1 ) from the artificially contaminated corn kernels with an indirect cold atmospheric pressure plasma (CAP) treatment generated with a surface barrier discharge system working in ambient air. Surface analysis of the corn kernels revealed the presence of minor changes in the treated samples, indicating that indirect CAP treatments induced slight oxidation of the corn kernel surface. This study not only proposes CAP as an effective food processing method for the decontamination of mycotoxins but also presents the first step towards acceptance of CAP technology as a safe food processing method. Abstract : This study reports on the removal of mycotoxins found in up to 80% of global food and feed crop. The complete removal was achieved for aflatoxin B1 (AFB1 ) from artificially contaminated corn kernels with an indirect cold atmospheric pressure plasma (CAP) treatment generated with a surface barrier discharge system working in ambient air. Surface analysis of the corn kernels revealed the presence of minor changes in the treated samples, indicating that indirect CAP treatments induced slight oxidation of the corn kernel surface. This study presents the first step towards the acceptance of CAP technology as a safe food processing method.